Kamuda Bir İstihdam Modeline Dönüşen Alt İşverenlik - (:unkn) unknown (My University, 2016)
İİş hukuku, işçi ve işveren arasındaki ilişkileri düzenleyen ve inceleyen bir hukuk dalıdır. İş hukukunda asıl olan işverenin kendi işçisi ile mal veya hizmet üretmesidir. Söz konusu işlerin başka işverenlere verilmesi istisnai durumdur ve ancak Kanunun öngördüğü sınırlar içerisinde gerçekleştirilebilir. Alt işverenlik, işverene işyerindeki mal veya hizmet üretimini başka bir işverenin işçileri vasıtasıyla gerçekleştirme imkânı sağlayan bir uygulamadır. Günümüzde yoğun bir uygulama alanı bulan alt işverenlik bir nevi "istihdam modeli" hüviyetine dönüşmüştür. Türkiye'de resmi kayıtlara göre yaklaşık 1,5 milyon alt işveren işçisi bulunmaktadır. Alt işveren işçilerinin ücret, kıdem tazminatı, yıllık izin gibi özlük haklarına yönelik sorunları bulunmaktadır. Son dönemde yapılan bazı yasal düzenlemelerle kamu kurum ve kuruluşlarda çalıştırılan alt işveren işçilerine yönelik ücret, kıdem tazminatı ve yıllık iznin haklarına ilişkin bir takım iyileştirmeler yapılmıştır. Bu çalışmada kamu sektöründe alt işveren işçilerinin sorunlarına yönelik tespitler, alt işverenliği doğuran sebepler, ortaya çıkan sorunlar ve çözüm önerileri güncel gelişmeler ışığında tartışılmıştı

Labour law is a branch of law that regulates and investigates the relationship between employers and employees. It is primary in the labour law that the main employer produces goods and service with its own employees. It is an exceptional case to sublet these works to other employers and this can be made within the limits that are stipulated by the law. Subcontracting is a practice which gives employers the opportunity to perform the production of goods or services in the workplace by another employer's employees.Subcontracting, which is finding itself intense application arena in today's world, has been transformed into the nature of an "employment model". According to the official records, there are existing 1.5 million subcontractor employees in today' Turkey.There are problems existing regarding employment rights of the subcontractor's employees, such as wages, severance payments, annual paid leave. With some legal arrangements in the last years, some improvements are being done in the employment rights of the subcontractor's employees who are working at public institutions and organisations, regarding wages, severance payments, and annual paid leave rights. In this study, determinations regarding problems of the subcontractor's employees' in the public sector, the reasons for subcontracting practices, the problems emerging from this practice, and solutions for this problems are being discussed within the light of current developments.
The Practice of Subcontracting which has Turned into an Employment Model in the Public Sector
Keywords: Uluslararası İlişkiler; Siyasi Bilimler